2022
DOI: 10.1101/2022.09.26.22280389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-Analysis Reveals the Vaginal Microbiome is a Better Predictor of Earlier Than Later Preterm Birth

Abstract: High-throughput sequencing measurements of the vaginal microbiome have yielded intriguing potential relationships between the vaginal microbiome and preterm birth (PTB; live birth prior to 37 weeks of gestation). However, results across studies have been inconsistent. Here we perform an integrated analysis of previously published datasets from 12 cohorts of pregnant women whose vaginal microbiomes were measured by 16S rRNA gene sequencing. Of 1926 women included in our analysis, 568 went on to deliver prematur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Metaanalysis as well as rigorous evaluation of models on independent validation data is a robust approach to contend with these biological challenges with microbiome data. However there are significant technical challenges in aggregating and combining microbiome data across studies, therefore there have been few studies taking on this task [30][31][32] . In previous work, we have shown that by aggregating microbiome data across several studies we can gain significant statistical power to show that higher diversity is associated with PTB especially in the first trimester of pregnancy and to identify several novel microbial associations 33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaanalysis as well as rigorous evaluation of models on independent validation data is a robust approach to contend with these biological challenges with microbiome data. However there are significant technical challenges in aggregating and combining microbiome data across studies, therefore there have been few studies taking on this task [30][31][32] . In previous work, we have shown that by aggregating microbiome data across several studies we can gain significant statistical power to show that higher diversity is associated with PTB especially in the first trimester of pregnancy and to identify several novel microbial associations 33 .…”
Section: Introductionmentioning
confidence: 99%
“…While ML approaches have been applied to the vaginal microbiome, most have involved a single dataset with limited sample size [34][35][36] . One recent work explored the application of ML to 12 vaginal microbiome datasets to predict PTB; however, while they leveraged public data extensively to ensure their findings were robust across studies, their work did not include an independent validation dataset 30 . Moreover, their work involved a single approach -a random forest ML model -with predictive accuracy for PTB ranging from 0.28 to 0.79.…”
Section: Introductionmentioning
confidence: 99%
“…A common bioinformatics workflow was used to define ASVs in each of these studies, yielding a total of 85 unique Gardnerella ASVs across all samples and all cohorts. 57 However, many of these variants were found in very few samples and at very low abundances (Figure S12). 99% of all Gardnerella reads were contained in just the top 5 ASVs, which correspond to G1-G5 described above.…”
Section: Resultsmentioning
confidence: 99%
“…13,14,[53][54][55][56] The sequencing data were processed uniformly as part of a larger meta-analysis effort. 57 Seven cohorts from six publications were assessed. Exact sequencing variants were resolved using DADA2 58 version 1.12.1.…”
Section: Gardnerella 16s Rrna Asvs In Previously Collected Cohortsmentioning
confidence: 99%
“…The bacteria associated with sPTB differ between studies and appear to vary significantly at the individual level, dependent on many factors, including specific combinations of bacteria, strains of bacteria, bacterial load, sites of bacterial localization, kinetics and timing of infection, the level of inflammation induced, as well as ethnicity and geographical region. 40,48 These differences hinder the development of accurate, universal diagnostics and effective strategies to treat women at risk of sPTB.…”
Section: Chlamydia Trachomatis Neisseria Gonorrhoeae Treponema Pallid...mentioning
confidence: 99%